ODACE-RMS: A Remote Web-Based Platform for Automated Multi-Device Android Testing and Certification - Sundos Mojahed; Rejean Drouin; Lokman Sboui (IEEE Access)
The evolving nature of the software industry has increased the complexity and cost of software testing. This paper highlights the critical need for automation in software testing, specifically for mobile Android device certification. We introduce ODACE-RMS, a platform designed to streamline the certification process by enabling the automated execution of comprehensive telecommunication test scenarios. ODACE-RMS runs as an application on a tester’s PC, featuring a browser-based interface powered by Appium. The paper also outlines ODACE-RMS’s modular architecture that combines Appium, ADB, and USB-over-IP to support remote and parallel testing. With a Spring Boot backend and web-based frontend, the platform enables flexible multi-device test sessions, whether connected locally via USB or remotely through a USB-over-IP hub. These features significantly reduce certification time and allow engineers to execute tests without physically handling devices. Our study compares ODACE-RMS with traditional systems, which reduced engagement time in certification testing by 89%, significantly decreasing the need for human intervention and enhancing the overall efficiency of the certification process. Additionally, the proposed ODACE-RMS architecture results show that testing remotely is not much slower than testing locally through physical ports, even when multiple devices are tested in parallel, with an average 7% delay.